Implementasi Peraturan Bupati Gunungkidul Nomor 36 Tahun 2015 Tentang Pencegahan Perkawinan Pada Usia Anak dalam Perspektif Maslahah Mursalah - Agung Ilham Affaruddin; Nurul Asiya Nadhifah (State Islamic University (UIN) of Sunan Ampel, 2019)
Regent Regulations (Perbup) of Gunungkidul Number 36 Year 2015 Concerning Prevention of Marriage at the Age of Child is a special regulation regarding the efforts, programs, actions, activities used by the government agencies of Gunungkidul Regency in order to prevent and reduce the number of marriages at the age of child. Wonosari Religious Court statistics show a decrease in the number of submissions for marriage dispensations from 2015 to 2017 after the enactment of this regulation. In 2015 there were 109 cases of marriage dispensation, in 2016 there were 85 cases of marriage dispensation, in 2017 there were 65 cases of marriage dispensation. In its implementation, this regulation has benefits because it forms the basis of human life (maslahah dharuriyyah). This regulation has also answered the problems that humans need to eliminate the difficulties they face (maslahah hajiyyah). In addition, this regulation has preserved the wisdom and goodness of manners and social and cultural beauty (maslahah tahsiniyyah). Seen from its implementation, Perbup Gunungkidul Number 36 of 2015 concerning Prevention of Marriage at the Age of Child is in accordance with the principles of problem solving.